PENGARUH PRODUCT DAN SERVICE QUALITY PADA CUSTOMER TRUST DAN DAMPAKNYA TERHADAP PURCHASE INTENTION STUDI KASUS: PT.INDOTEHNIK CIPTA SEMBADA - Aryo Bismo; Yonathan Gunawan (Universitas Pembangunan Nasional Veteran Yogyakarta, 2019)
The purpose of this study was to determine the effect of product quality and service quality through customer trust on purchase intention at PT. IndoTehnik Cipta Sembada. The data collection method is using questionnaire that distributed to people who already made a purchase or have an electric panel that sold by PT. Indotehnik Cipta Sembada. The analysis method used on this research is path analysis. The results achieved that service quality and customer trust has relationship while on the other hand there is no relationship between product quality and customer trust another result was there is no relationship between product quality toward purchase intention it is followed by there is no relationship between service quality to purchase intention, and there is no relationship between customers trust in purchase intention indirectly, to conclude, in this case there is only service quality that has significant and positive effect towards customer trust. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh product quality dan service quality melalui customer trust terhadap purchase intention di PT. IndoTehnik Cipta Sembada. Metode pengumpulan data adalah dengan menggunakan kuisioner yang disebarkan ke orang – orang yang pernah melakukan pembelian atau memiliki panel listrik yang dijual oleh PT. IndoTehnik Cipta Sembada. Metode analisis yang digunakan adalah path analysis, hasil yang dicapai adalah adanya hubungan antara variable service quality terhadap customer trust, tidak adanya hubungan antara product quality terhadap customer trust, tidak adanya hubungan antara product quality terhadap purchase intention, tidak adanya hubungan antara service quality terhadap purchase intention, dan tidak adanya hubungan antara customer trust terhadap purchase intention.